DEVELOPING STUDENT COMPETENCIES THROUGH A CREATIVE APPROACH TO TEACHING ELEMENTARY PROGRAMMING - Yuldash Abdullayevich Kuralov (Web of Journals Publishing, 2024)
This article presents suggestions and recommendations for teaching students programming languages and forming their programming competence based on the competency approach.
Keywords: Programming, competence, competence, practical program, computer.